Manifeste cyborg et autres essais : sciences, fictions, féminismes - Haraway, Donna Jeanne (Exils, 2007)
La fin du XXe siècle, notre époque, ce temps mythique, est arrivé et nous ne sommes que chimères, hybrides de machines et d'organismes théorisés puis fabriqués ; en bref, des cyborgs. Le cyborg est notre ontologie ; il définit notre politique. Le cyborg est une image condensée de l'imagination et de la réalité matérielle réunies, et cette union structure toute possibilité de transformation historique. Dans la tradition occidentale des sciences et de la politique, tradition de domination masculine, raciste et capitaliste, tradition de progrès, tradition de l'appropriation de la nature comme ressource pour les productions de la culture, tradition de la reproduction de soi par le regard des autres, la relation entre organisme et machine fut une guerre de frontières... " Ainsi parle Donna Haraway. Ses textes traduits en plus de 16 langues en font une autrice incontournable de la scène intellectuelle internationale, penseuse de la postmodernité et des technosciences. La plus grande partie de son oeuvre est encore inédite en français. Bienvenue dans le monde de Donna Haraway peuplé de cyborgs, hybrides, femalemen, oncomice, coyotes et autres monstres. Il s'y déjoue les dichotomies anciennes : féminin / masculin ; nature / culture ; vivant / artefact. Bienvenue dans le monde de Donna Haraway, ses fabulations sont les nôtres, nos pires craintes ou nos meilleures espérances ? A l'évidence, les cartes politiques pour l'invention de nouveaux espaces. Cette anthologie propose les textes essentiels de Donna Haraway : Cyborg Manifeste, Situated Knowledge, Teddy Bear Patriarchy, Ecce Homo, Modest Witness, Race.
Keywords: LGBTQIA2+; anthologie; approches et analyses; corps; cours; cyborg; discipline; discours dominant; fem1000; fem3600; féminisme cyborg; genre; har4600; identités LGBTQIA2+; ontologie; patriarcat; point de vue situé; premier cycle; sciences humaines; systèmes d'oppressions; thématiques

Manifeste cyborg : science, technologie et féminisme socialiste à la fin du 20e siècle - Haraway, Donna Jeanne (Manifeste cyborg et autres essais : sciences, fictions, féminismes, 2007)
Première publication: 1991
Keywords: amériques; approches et analyses; corps; cours; discours dominant; fem1000; féminisme cyborg; genre; identités LGBTQIA2+; point de vue situé; premier cycle; régions géographiques; systèmes d'oppressions; technologie; thématiques; états-unis

Veil: veiling, representation, and contemporary art - Tawadros, Gilane; Bailey, David A. (MIT Press ; IVA, 2003)
No single item of clothing has had greater influence on Western images of Middle Eastern and North African women than the veil. The fascination of Western writers, artists, and photographers with the veil reflects the voyeuristic nature of our interest in what is strange and "other." Veil, which accompanies an exhibition organized by the Institute of International Visual Arts in London, explores the representation of the veil in contemporary visual arts. Providing a context for the commissioned essays are a number of classical historical texts crossing religions, cultures, genders, and ages–from Greek myths to articles published in the aftermath of September 11, 2001. Some of the contemporary artists and scholars write autobiographically about the meaning of the veil in their lives. Others take a more political approach, discussing, for example, how the events of September 11 changed the use and reception of veil imagery throughout the world. Still others take a historical approach, examining how nineteenth-century technological developments in travel and photography led to photographic depictions of both the veiled and unveiled body in relation to landscape. A number of essays look at the art historical precedents for the current interest in artwork addressing the veil, while others examine how codes of modesty and gender segregation have affected the making and viewing of films in postrevolutionary Iran. The essays are by Jananne Al-Ani, David A. Bailey, Alison Donnell, Ghazel, Salah Hassan, Reina Lewis, Hamid Naficy, Zineb Sedira, and Gilane Tawadros. The artists represented include Faisal Abdu'Allah, Kourosh Adim, Ghada Amer, Jananne Al-Ani, Farah Bajull, Samta Benyahia, Gaëtan de Clérambault, Marc Garanger, Shadafarin Ghadirian, Group AES, Emily Jacir, Ramesh Kalkur, Shirin Neshat, Harold Offeh, Gillo Pontecorvo, Zineb Sedira, Mitra Tabrizian, and Elin Strand.
Section: 187 p. : illustrations en noir et en coul. ; 22 cm
Keywords: afrique; afrique du nord; approches et analyses; arts; corps; cours; discipline; féminisme islamique; har4610; histoire de l'art; mode; moyen-orient; point de vue situé; premier cycle; régions géographiques; thématiques; vêtements

The female circumcision controversy: an anthropological perspective - Gruenbaum, Ellen (University of Pennsylvania Press, 2001)
To the Western eye, there is something jarringly incongruous, even shocking, about the image of a six-year-old girl being held down by loving relatives so that her genitals can be cut. Yet two million girls experience this each year. Most Westerners, upon learning of the practice of female circumcision, have responded with outrage; those committed to improving the status of women have gone beyond outrage to action by creating various programs for "eradicating" the practice. But few understand the real life complexities families face in deciding whether to follow the traditional practices or to take the risk of change. InThe Female Circumcision Controversy, Ellen Gruenbaum points out that Western outrage and Western efforts to stop genital mutilation often provoke a strong backlash from people in the countries where the practice is common. She looks at the validity of Western arguments against the practice. In doing so, she explores both outsider and insider perspectives on female circumcision, concentrating particularly on the complex attitudes of the individuals and groups who practice it and on indigenous efforts to end it. Gruenbaum finds that the criticisms of outsiders are frequently simplistic and fail to appreciate the diversity of cultural contexts, the complex meanings, and the conflicting responses to change. Drawing on over five years of fieldwork in Sudan, where the most severe forms of genital surgery are common, Gruenbaum shows that the practices of female circumcision are deeply embedded in Sudanese cultural traditions-in religious, moral, and aesthetic values, and in ideas about class, ethnicity, and gender. Her research illuminates both the resistance to and the acceptance of change. She shows that change is occurring as the result of economic and social developments, the influences of Islamic activists, the work of Sudanese health educators, and the efforts of educated African women. That does not mean that there is no role for outsiders, Gruenbaum asserts, and she offers suggestions for those who wish to help facilitate change. By presenting specific cultural contexts and human experiences with a deep knowledge of the tremendous variation of the practice and meaning of female circumcision, Gruenbaum provides an insightful analysis of the process of changing this complex, highly debated practice.
Section: 242 p. ; 23 cm
Keywords: afrique; anthropologie; approches et analyses; corps; cours; discipline; histoire et politique; justice sociale; point de vue situé; premier cycle; ressource en ligne; régions géographiques; santé; sciences humaines; sex2283; soudan; système colonial; systèmes d'oppressions; thématiques; violences

Les pratiques traditionnelles affectant la santé physique et mentale des femmes; l'excision et l'infibulation - situation actuelle et perspectives d'avenir - Vissandjée, B.; Ndejuru, R.; Kantiébo, M.; Renaud, J.; Aïthachimi, L.; Levine, L.; Lapointe, M. (Institut universitaire SHERPA, 2001)
L’excision et l’infibulation sont parties intégrantes des traditions de nombreuses sociétés africaines issues majoritairement de la région subsaharienne. En contexte canadien, aucune information statistique n’est présentement disponible sur la prédominance de cette pratique, malgré le fait que de nombreux intervenants soupçonnent que plusieurs immigrant(e)s en provenance de ces pays sont susceptibles de faire subir ces pratiques à leurs fillettes. Cette étude qualitative explore les valeurs et les croyances des immigrant(e)s par rapport à ces pratiques traditionnelles, tout en cernant les défis de leur processus d’intégration au Canada et leur recours aux services de santé.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; canada; care; corps; cours; discipline; interculturalité; migration; médecine; point de vue situé; premier cycle; périodes historiques; québec; régions géographiques; sciences; sciences humaines; sciences infirmières; sex2283; sexologie; sexualité; thématiques; violences